Biology of Prochiloneurus insolitus (Alam) (Hymenoptera, Encyrtidae), a hyperparasitoid on mealybugs (Homoptera, Pseudococcidae): immature morphology, host acceptance and host range in west Africa - Goergen, Georg E.; Neuenschwander, Peter (1990)
The endophagous hyperparasitoid Prochiloneurus insolitus (Alam) was offered various stages of Epidinocarsis lopezi (De Santis), a primary parasitoid of the cassava mealybug (CM) Phenacoccus manihoti (Matile-Ferrero). Embryos were surrounded by a trophamnion. Larval development involved four instars, and adult females emerged after 11.2 days at 27°C. In a choice experiment parasitized and unparasitized CM of different instars were attacked with equal frequency, though no egg was ever laid into unparasitized CM. Stung CM without an immature wasp suffered from increased mortality and had a reduced oviposition capacity compared to those not attacked by the hyperparasitoid. CM wax and ovisacs were the main attractant in locating the secondary host, and older CM instars were preferred over younger ones. The attack of P. insolitus is stimulated by physical cues from unrelated secondary hosts. Oviposition is induced by chemical stimuli of primary encyrtid hosts